Intraoperative Round Window Electrocochleography and Speech Perception Outcomes in Pediatric Cochlear Implant Recipients. (2nd September 2014) - Formeister, Eric J.; McClellan, Joseph H.; Merwin, William H.; Iseli, Claire E.; Buchman, Craig A.; Fitzpatrick, Douglas; Adunka, Oliver F.
Abstract : Objectives: (1) Understand how intraoperative electrocochleograpy (ECoG) is used for assessing residual cochlear function in pediatric implant recipients. (2) Appreciate the utility of electrocochleograpy in predicting speech perception outcomes. Methods: A prospective cohort study of pediatric cochlear implant patients at a tertiary hospital was conducted starting in July 2011 and is ongoing. ECoG recordings were obtained from 77 children (89 ears) during cochlear implantation and provided a total response metric that can quantify the underlying hair cell and neural health. Follow‐up speech perception tests were conducted at ≥7 months postoperatively with the phonetically balanced kindergarten (PB‐k) word lists (n = 24). PB‐k scores were compared to ECoG total response and other clinical and audiologic variables using multiple linear regression analysis in order to construct a parsimonious model for predicting speech outcomes. Results: Postoperative PB‐k scores were significantly correlated with ECoG total response ( r 2 = 0.32, P =. 006) and preoperative pure tone averages (PTA; r 2 = 0.41, P =. 001). ECoG total response was weakly and inversely correlated with PTA ( r 2 = 0.14, P =. 001, n = 89). Hierarchical multiple linear regression identified a model for speech perception performance that included preoperative PTA, duration of cochlear implant use, and ECoG total response that predicted about half of the variance in PB‐k performance (adjusted r 2 = 0.49, P =. 002). Conclusions: Intraoperative ECoG recordings are significantly correlated with speech perception outcomes in pediatric cochlear implant recipients and alone can account for a similar proportion of variance in speech perception when compared to other bioaudiometric factors. ECoG provides useful prognostic information about attainment of open set speech perception in children.